Estimating quantities and sources of marine debris at a continental scale. Issue 1 (22nd December 2016) - Hardesty, Britta Denise; Lawson, TJ; van der Velde, Tonya; Lansdell, Matt; Wilcox, Chris
Abstract : Marine debris is recognized as an important global issue that can negatively affect wildlife, habitats, environmental processes, ecosystem services, and human activities including tourism, fishing, and navigation. To improve understanding of the sources and impacts of marine debris, we carried out a national litter survey at 175 sites around Australia using a stratified random sampling approach. Litter from land‐ and sea‐based sources is ubiquitous, and sampling effects related to coastline shape, substrate characteristics, gradient, and backshore type were highly significant. Source effects related to land‐based sources (eg population density and distance to road) were also highly significant. Of the total debris sampled, approximately 75% was plastic; 2% was related to recreational fishing. Litter density significantly increased with proximity to urban areas, suggesting a domestic origin; statistical patterns suggest that illegal rubbish disposal is a major driver. By quantifying debris at a large scales and distinguishing potential litter sources, we can better develop scale‐appropriate solutions to reduce debris inputs to the environment.